Carbon-free dry reforming of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh; Joshi, Upendra A. (Catalysis Letters, 2005)
CoNdOx (Co/Nd = 1) is a highly promising catalyst for the carbon-free CO2 reforming of methane. Influence of the Co/Nd ratio on the catalyst performance in the CO2 reforming and also on the crystalline phases and reduction by temperature programmed reduction (TPR) of the CoNdOx catalyst has also been investigated. The CoNdOx (CoNd = 1.0) catalyst consisted of mainly NdCoO3 perovskite- type mixed metal oxide and it showed not only a high resistance to carbon formation at different process conditions ( viz. temperature = 750 - 900 degrees C and gas hourly space velocity (GHSV) = 10000 - 50000 cm(3) g(-1) h(-1)) but also high activity and selectivity in the CO2 reforming process. The high resistance to carbon formation for this catalyst is attributed mostly to strong metal (Co degrees) - support (Nd2O3) interactions.
Keywords: CO2 reforming of methane to syngas; CoNdOx catalyst; NdCoO3 perovskite; resistance to carbon formation in CO2 reforming

Epoxidation of styrene by anhydrous hydrogen peroxide over boehmite and alumina catalysts with continuous removal of the reaction water - Choudhary, Vasant R.; Patil, N. S.; Chaudhari, Nitin K.; Bhargava, Suresh Kumar (Journal of Molecular Catalysis A-Chemical, 2005)
Boehmite and alumina (obtained from the boehmite by its calcination at different temperatures 300-900degreesC) are active and stable catalysts for the selective epoxidation of styrene by anhydrous H2O2 to styrene oxide with continuous removal of the reaction water. Influence of the catalyst (boehemite) calcination temperature, H2O2/styrene ratio and catalyst loading on the styrene conversion and selectivity for styrene oxide. phenyl acetaldehyde. benzaldehyde and benzoic acid in the epoxidation has been investigated. In the presence of water. the catalyst shows very poor activity and selectivity in the epoxidation. The catalyst also catalyses H2O2 decomposition and hence has optimum loading for obtaining high-styrene conversion in the epoxidation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Alumina; anhydrous hydrogen peroxide; boehmite; Epoxidation of styrene; Styrene oxide

Green process for chlorine-free benzaldehyde from the solvent-free oxidation of benzyl alcohol with molecular oxygen over a supported nano-size gold catalyst - Choudhary, Vasant R.; Dhar, A.; Jana, Prabhas; Jha, Rani; Uphade, B. S. (Green Chemistry, 2005)
Benzyl alcohol is oxidized selectively to benzaldehyde with high yield, with a little formation of benzylbenzoate, by molecular oxygen over a reusable nano-size gold catalyst supported on U3O8, MgO, Al2O3 or ZrO2 in the absence of any solvent.

Highly active and reusable catalyst from Fe-Mg-hydrotalcite anionic clay for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Choudhari, P. A. (Journal of Chemical Sciences, 2005)
Fe-Mg-hydrotalcite (Mg/Fe = 3) anionic clay with or without calcination (at 200-800 degrees C) has been used for the benzylation of toluene and other aromatic compounds by benzyl chloride. Hydrotalcite before and after its calcination was characterized for surface area, crystalline phases and basicity. Both the hydrotalcite, particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 200-800 degrees C show high catalytic activity for the benzylation of toluene and other aromatic compounds. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of iron on the catalyst surface.
Keywords: activation by calcinations; benzylation of aromatic compounds; benzylation of toluene; Fe-Mg-hydrotalcite

High-temperature stable and highly active/selective supported NiCoMgCeOx catalyst suitable for autothermal reforming of methane to syngas - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh (Journal of Catalysis, 2005)
Low-surface-area, macroporous, zirconia-haffnia-supported NiCoMgOx and NiCoMgCeOx (Ni/Co/Mg/Ce = 1/0.2/1.2/0.0 or 1.2) catalysts, precalcined at high temperature ( 1400 degrees C for 4 h), showed both high activity (> 98% conversion) and selectivity ( > 95%) in the catalytic partial oxidation of methane (CPOM) to syngas. Their performance remained unchanged even after they were subjected to higher temperature (> 2000 degrees C for 30 min) or a number of high-temperature (> 2000 degrees C) shocks, due to their direct exposure to an oxyacetylene flame. The supported NiCoMgCeOx, however, showed superior performance in the steam and CO2 reforming reactions because of its much higher lattice oxygen mobility. Hence it is more suitable for the autothermal reforming of methane. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: autothermal reforming of methane; Catalyst; catalytic partial oxidation of methane; CO2 reforming of methane; high-temperature stable supported NiCoMgCeOx catalyst; steam reforming of methane; zirconia-haffnia-supported NiCoMgCeOx catalysts; zirconia-haffnia-supported NiCoMgOx

Hydrogen peroxide formation in the interaction of oxygen with boron-containing Pd catalysts prereduced by hydrazine in aqueous acidic medium containing bromide anions - Choudhary, Vasant R.; Samanta, C. (Catalysis Letters, 2005)
Interaction of molecular oxygen with Pd/BPO4 or ZrO2 (or Al2O3, CeO2, TiO2) - B2O3 catalysts, prereduced by hydrazine hydrate, in an aqueous acidic (H2SO4 or H3PO4) reaction medium containing bromide ions leads to the formation of H2O2. However, in the absence of boron in the catalyst and also in the absence of acid and/or bromide ions in the reaction medium, almost no H2O2 is formed.
Keywords: boron-containing Pd catalysts; Hydrogen peroxide; oxygen-catalyst interactions

Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization

Influence of PdO content and pathway of its formation on methane combustion activity - Choudhary, Tushar V.; Banerjee, S.; Choudhary, Vasant R. (Catalysis Communications, 2005)
The methane oxidation reaction is known to induce changes in the surface structure and composition of Pd catalysts; making it extremely arduous to relate the methane oxidation activity to specific catalyst properties by conventional methods (continuous flow reactor studies). To circumvent this, methodical pulse reactor studies have been undertaken to obtain correlations between the initial methane combustion activity and the catalyst properties (Pd-0/PdO content and path of PdO formation). While the initial methane combustion activity (at 160-280 degreesC) continuously increased with increasing PdO concentration (0-100%) in the catalyst, it continuously decreased with increasing Pddegrees content (0-100%). Controlled studies were undertaken to obtain catalysts with identical PdO content by two pathways: (i) by controlled partial oxidization of Pd-0/Al2O3 and (ii) by controlled partial reduction of PdO/Al2O3. Interestingly, for a given PdO content, the catalysts obtained by partial oxidation of Pd-0/Al2O3 showed a significantly superior performance to the catalyst obtained by partial reduction of PdO/Al2O3 for all the temperatures investigated. These studies unambiguously show that along with the relative concentration of PdO, the PdO formation pathway is also critical in deciding the methane combustion activity of the catalyst. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Methane combustion; Oxidation; partially oxidized Pd-0/Al2O3; partially reduced PdO/Al2O3; Pd-0/Al2O3; PdO/Al2O3; pulse reaction of methane

In-Mg-hydrotalcite anionic clay as catalyst or catalyst precursor for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Narkhede, V. S. (Journal of Molecular Catalysis A-Chemical, 2005)
In-Mg-hydrotalcite (Mg/In = 3) anionic clay with or without calcination (at 200-800 degrees C) or HCl pretreatment at different temperatures (26 and 80 degrees C) and periods (0.1 or 1.0 h) has been used for the benzylation of benzene and/or substituted benzenes by benzyl chloride. The hydrotalcite before and after its calcination or HCl pretreatment was characterized for its surface area, crystalline phases and basicity. The hydrotalcite particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 800 degrees C followed by HCl pretreatment (at 80 degrees C for 1.0 h), shows high catalytic activity even for the benzylation of benzene. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of indium on the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: activation of In-Mg-hydrotalcite by calcination; activation of In-Mg-hydrotalcite by HCl pretreatment; benzylation of benzene; benzylation of substituted benzenes; In-Mg-hydrotalcite

Kinetics of the complete combustion of dilute propane and methyl ethyl ketone over Cr-doped ZrO2 catalyst - Choudhary, Vasant R.; Deshmukh, G. M. (Chemical Engineering Science, 2005)
The kinetics of the complete combustion of propane and methyl ethyl ketone (MEK) at very low concentration in air (0.45 and 0.4 mol% in air, respectively) over Cr-doped ZrO2 (cubic) catalyst (Cr/Zr = 0.25) at different temperatures (485-673 K) in the kinetic control regime have been investigated. The combustion rate data could be fitted well to both the power law and redox (Mars-Van Krevelen) models. From the power law model, the apparent activation energy for the combustion of propane and MEK has been found to be 16.5 and 13.2 kcal mol(-1), respectively. Among the two models, the redox one, however, gave a better fit to the kinetic data for both the combustion of propane and MEK. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: combustion kinetics; combustion of methyl ethyl ketone; combustion of propane; Cr-doped ZrO2 (cubic) catalyst; methyl ethyl ketone; propane

Kinetics of the complete combustion of dilute propane and toluene over iron-doped ZrO2 catalyst - Choudhary, Vasant R.; Deshmukh, G. M.; Mishra, D. P. (Energy & Fuels, 2005)
The kinetics of the complete combustion of propane and toluene at very low concentrations in air (0.45 and 0.3 mol % in air, respectively) over iron-doped ZrO2 (cubic) catalyst (Fe/Zr = 0.25) at different temperatures (598-723 K) in kinetic control regime have been investigated. The combustion rate data could be fitted very well to both the power-law and redox (Mars-Van Krevelen) models. However, the redox model provided a better fit to the kinetic data for the propane combustion. It also showed a better fit to the toluene combustion data at the lower temperatures (623 K). The reaction order (with respect to the hydrocarbon), apparent activation energy, and frequency factor (from the power-law model) for the propane combustion were 0.96 (average), 21.16 kcal/mol, and 4.67 x 10(5) Mol g(-1) h(-1) kPa(-n), respectively, and those for the toluene combustion were 0.77 (average), 26.08 kcal/mol, and 1.48 x 10(7) mol g(-1) h(-1) kPa(-n), respectively.

Low temperature complete combustion of dilute toluene and methyl ethyl ketone over Mn-doped ZrO2 (cubic) catalysts - Choudhary, Vasant R.; Deshmukh, G. M.; Pataskar, S. G. (Journal of Chemical Technology and Biotechnology, 2005)
Combustion of dilute toluene and methyl ethyl ketone over Mn-doped ZrO2 catalysts prepared using different precipitating agents, such as tetra-alkyl ammonium hydroxides and NH4OH, having Mn/Zr ratios from 0.05 to 0.67, and calcined at different temperatures has been thoroughly investigated. The Mn-doped ZrO2 catalyst shows high toluene or methyl ethyl ketone combustion activity, particularly when its ZrO2 is in cubic form, when its Mn/Zr ratio is close to 0.2, and when it is prepared using tetra-methyl ammonium hydroxide as a precipitating agent and calcined at 773 K. (c) 2005 Society of Chemical Industry.
Keywords: combustion of methyl ethyl ketone; combustion of toluene; Mn-doped ZrO2 catalyst

Low-temperature complete combustion of a dilute mixture of methane and propane over transition-metal-doped ZrO2 catalysts: effect of the presence of propane on methane combustion - Choudhary, Vasant R.; Deshmukh, G. M.; Pataskar, S. G. (Environmental Science and Technology, 2005)
Complete combustion of dilute methane alone or a dilute mixture of methane and propane over transition-metal (viz. Mn, Co, Cr, Fe, and Ni)-doped ZrO2 (cubic) catalysts at different temperatures (523-873 K) and a space velocity of 51 000 CM3 center dot g(-1)center dot h(-1) has been investigated for controlling methane and propane emissions from exhaust gases. The catalysts are compared for their catalytic ignition temperature and activity in the combustion of propane and methane in the presence of each other. The methane combustion activity of all the catalysts is strongly influenced by the presence of propane; it is decreased markedly. In the combustion of mixed methane and propane the Mn-doped ZrO2 and Cr-doped ZrO2 catalysts show the highest activity in the combustion of methane and propane, respectively; the Ni-doped ZrO2 shows the lowest activity in both cases. In the combustion of mixed methane and propane the propane combustion is enhanced but the methane combustion retarded when the Cr-doped ZrO2 and Mn-doped ZrO2 catalysts in a 1:1 ratio are used together in different ways (mixed or in layers).

Novel route for in-situ H2O2 generation from selective reduction of O-2 by hydrazine using heterogeneous Pd catalyst in an aqueous medium - Choudhary, Vasant R.; Samanta, C.; Jana, Prabhas (Chemical Communications, 2005)
Hydrogen peroxide in high yields can be generated with high efficiency at mild conditions (25 degrees C and atmospheric pressure) with the formation of only environment-friendly by-products (N-2 and H2O) by a reduction of O-2 by hydrazine from its hydrate/salt with its complete conversion in a short reaction period (<= 0.5 h) using a easily separable supported Pd catalyst (Pd/Al2O3, Pd/Ga2O3 or Pd/C) in an acidic aqueous medium in the presence of bromide anions; the presence of both acid (protons) and bromide anions is essential for the selective reduction of O-2 by hydrazine to H2O2 and in their absence, the reaction leads only to the formation of water.

Simultaneous conversion of methane and methanol into gasoline over bifunctional Ga-, Zn-, In-, and/or Mo-modified ZSM-5 zeolites - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Angewandte Chemie-International Edition, 2005)
Keywords: gallium; heterogeneuos catalysis; methane activation; Molybdenum; zeolites

CO2 reforming of methane combined with steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal-oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C. (Applied Energy, 2006)
CO2 reforming with simultaneous steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst (prereduced by H-2) at different process conditions has been investigated. In the simultaneous CO2 and steam reforming, the conversion of methane and H2O and also the H-2/CO product ratio are strongly influenced by the CO2/H2O feed-ratio. In the simultaneous CO2 reforming and partial oxidation of methane, the conversion of methane and CO2, H-2 selectivity and the net heat of reaction are strongly influenced by the process parameters (viz. temperature, space velocity and relative concentration of O-2 in the feed). In both cases, no carbon deposition on the catalyst was observed. The reduced NdCoO3 perovskite-type mixed-oxide catalyst (Co dispersed on Nd2O3) is a highly promising catalyst for carbon-free CO2 reforming combined with steam reforming or partial oxidation of methane to syngas. (c) 2005 Published by Elsevier Ltd.
Keywords: Co/Nd2O3 catalyst; methane; NdCoO3 perovskite-type mixed metal-oxide catalyst; Oxy-CO2 reforming of methane; simultaneous CO2 and steam reforming of methane

CO2 reforming of methane to syngas over CoOx/MgO supported on low surface area macroporous catalyst carrier: Influence of Co loading and process conditions - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Industrial & Engineering Chemistry Research, 2006)
The effect of Co loading (5-30 wt %) and process parameters ( reduction pretreatment, reaction temperature, and space velocity) have been investigated over CoOx/MgO(5%)/SA-5205 catalyst for the CO2 methane reforming process. The Co loading had a profound effect on the methane conversion and the hydrogen selectivity ( initial and time-on-stream activity) for the unreduced catalysts. While negligible methane conversion was observed for the 5 and 10 wt % Co loading catalyst, methane conversions > 95% were obtained over the high Co loading ( 20 and 30 wt %) catalysts; hydrogen selectivity followed the same trend as methane conversion. The Co loading level had a relatively smaller influence in the case of the reduced catalysts. While the 5 wt % Co catalyst showed low methane conversion activity (< 30%), the 10 wt % Co catalyst showed methane conversion levels comparable to those of the high Co loading catalysts. The high Co loading catalysts showed an excellent time-on-stream performance for the CO2 methane reforming reaction. X-ray diffraction and temperature-programmed reduction experiments indicate that the interesting activity behavior exhibited by the catalysts is related to the different phases ( and their reducibility) present in the catalysts at different Co loadings. The hydrogen selectivity was found to decrease with decreasing reaction temperature and increasing space velocity due to the increased simultaneous occurrence of the reverse water-gas shift reaction along with the CO2 reforming reaction.

Direct oxidation of H-2 to H2O2 over Pd-based catalysts: influence of oxidation state, support and metal additives - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
The influence of oxidation state (reduced and oxidized), support (ZrO2, Ga2O3, CeO2, SiO2, H-beta, ThO2, CeO2-ZrO2, BPO4 and Pd/Al2O3) and precious metal additives (Au, Pt, Rh and Ru) on the direct H2O2 synthesis has been investigated over Pd-based catalysts. For all the supports investigated herein, the oxidized Pd catalysts showed significantly superior H2O2 yields as compared to their reduced counterparts. The effect of the Pd oxidation state was found to be more important for determining the H2O2 yields than the particle size and surface area properties of the catalyst system. An excellent correlation was observed between the H2O2 selectivity and H2O2 decomposition activity of the oxidized Pd catalysts. The oxidized Pd catalysts showed almost an order of magnitude lower H2O2 decomposition activity than the reduced catalysts. The H2O2 yield in the H-2 to H2O2 oxidation passed through a maximum with increase in the An concentration. Although a similar effect was also observed in case of Pt, Au was found to be a superior promoter for the direct H2O2 synthesis process. Addition of Rh and Ru was found to be detrimental for the H2O2 yields; these results can be explained in terms of increased H2O2 decomposition activity and/or enhanced H-2 to H2O reaction activity in their presence. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: decomposition; direct synthesis; H2O2; metal additives; oxidation state; Pd catalysts; supports

Factors influencing decomposition of H2O2 over supported Pd catalyst in aqueous medium - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Journal of Molecular Catalysis A-Chemical, 2006)
Since H2O2 decomposition can result in selectivity/yield loss in the direct H2O2 synthesis process from H-2 and O-2 over supported Pd catalysts, it is important to have an enhanced understanding about the factors affecting the H2O2 decomposition reaction. Herein, detailed studies have been undertaken to investigate the influence of different factors, such as (a) nature and concentration of acid in reaction medium, (b) nature and concentration of halide in presence and absence of acid in reaction medium, (c) pretreatment procedures and (d) catalyst modification by incorporation of different halides, on the H2O2 decomposition reaction over a 5% Pd/C catalyst in aqueous medium at 25 degrees C. This study has shown that the H2O2 decomposition activity is profoundly influenced by all the above factors. The effectiveness of the acids in suppressing the H2O2 decomposition activity decreased in the following order: hydroiodic acid > hydrobromic acid > hydrochloric acid >> acetic acid > phosphoric acid > sulfuric acid > perchloric acid. The ability of the acid to decrease the H2O2 decomposition activity was found to very strongly depend on the nature of its associated anion. Halides, such as iodide, bromide and chloride were particularly effective in suppressing the H2O2 decomposition activity. Oxidation pretreatment of the catalyst was found to strongly suppress its H2O2 decomposition activity, while a reduction treatment was found to promote its activity. A gradual decrease in the H2O2 decomposition activity of the catalyst was observed with each successive usage due to in situ sub-surface oxidation of Pd by H2O2. Halide incorporation either via the reaction medium or prior catalyst modification had a similar qualitative effect on the H2O2 decomposition activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acid; H2O2 decomposition; H2O2 synthesis; halides; Pd catalysts; pretreatment

Methane reforming over a high temperature stable-NiCoMgOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Chemical Engineering Journal, 2006)
The unusually high temperature stable NiCoMgOx (Ni/Co/Mg: 1:0.2:1.2)/zirconia-hafnia catalyst has been investigated for syngas generation via the catalytic partial oxidation of methane (CPOM), oxidative steam reforming of methane (OSRM) and oxidative CO2 reforming of methane (OCRM) processes. The catalyst, even when calcined at 1400 degrees C for 4 h, showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions. On account of its high thermal stability, hot spots in the catalyst bed and/or high temperatures prevailing at the catalyst surface during the oxy-reforming processes would have little or no effect on the catalytic activity/selectivity of the NiCoMgOx/zirconia-hafnia catalyst, thus making the catalyst suitable even for operating under adiabatic conditions. While the selectivity for CO increased considerably with increasing reaction temperature for the CPOM process, the selectivity for H-2 was affected to a much lesser extent. The selectivity for CO and H-2 in the CPOM reaction was found to decrease with increasing space velocity; the H-2 selectivity was however affected to a greater extent. For the OSRM process, the H2O/CH4 ratio profoundly influenced the H-2/CO ratio and the heat of the reaction. Depending on the H2O/CH4 ratio, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion increased rapidly with increasing OCRM temperature and correspondingly the exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. At 900 degrees C, the OCRM reaction was mildly exothermic and provided high methane conversion and syngas selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: high temperature stable catalyst; methane; oxy-dry reforming; oxy-steam reforming; Partial oxidation

Non-catalytic pyrolysis of ethane to ethylene in the presence of CO2 with or without limited O-2 - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Journal of Chemical Science, 2006)
Influence of the presence Of CO2, which is a mild oxidant, on the performance of the thermal cracking of ethane to ethylene in the absence or presence of limited O-2 at different temperatures (750-900 degrees C), space velocities (1500-9000 h(-1)) and CO2/C2H6 and O-2/C2H6 mole ratios (0-2.0 and 0-0.3 respectively) has been investigated. In both the presence and absence of limited 02, ethane conversion increases markedly because of the presence Of CO2, indicating its beneficial effect on the ethane to ethylene cracking. The increased ethane conversion is, however, not due to the oxidation of ethane to ethylene by CO2; the formation of carbon monoxide in the presence Of CO2 is found to be very small. It is most probably due to the activation of ethane in the presence Of CO2.
Keywords: ethane; ethane cracking in presence Of CO2; ethane cracking in presence of CO2 and limited O-2; Ethylene; thermal cracking of ethane

Oxy-CO2 reforming of methane to syngas over CoOx/CeO2/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Energy & Fuel, 2006)
The oxy-CO2 methane reforming (OCRM) process has been investigated over the CoOx/CeO2/SA-5205 catalyst at varying reaction temperatures (750-900 degrees C), O-2/CH4 ratios (0.3- 0.45), and space velocities (20 000 - 100 000 cm(3)/g/h). With an increasing OCRM reaction temperature, the contribution from the CO2 methane reforming reaction increased while that from methane combustion reactions decreased. Correspondingly, there was an increase in the H-2/CO ratio and a sharp decrease in reaction exothermicity. At 900 C (gas hourly space velocity = 46 000 cm(3)/g/h and O-2/CH4 = 0.4), the OCRM reaction over the CoOx/CeO2/SA-5205 catalyst was mildly endothermic with > 90% CH4 conversion, > 95% H-2 selectivity, and a H-2/CO ratio of 1.63. CH4 conversion was relatively unaffected by the O-2/CH4 ratio used in the OCRM reaction; however, CO2 conversion decreased on increasing the O-2/CH4 ratio. While H-2 selectivity was not significantly affected by the O-2/CH4 ratio, the H-2/CO ratio increased linearly with an increasing O-2/CH4 ratio. The endothermicity of the reaction was found to decrease with an increasing CH4/O-2 ratio, which can be explained on the basis of increased contribution from the methane partial oxidation reaction with an increasing O-2/CH4 ratio.

Oxy-CO2 reforming of methane to syngas over CoOx/MgO/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Fuel, 2006)
The OXY-CO2 methane reforming reaction (OCRM) has been investigated over CoOx supported on a MgO precoated highly macroporous silica-alumina catalyst carrier (SA-5205) at different reaction temperatures (700-900 degrees C), O-2/CH4 ratios (0.3-0.45) and space velocites (20,000-100,000cc/g/h). The reaction temperature had a profound influence on the OCRM performance over the CoO/MgO/SA-5205 catalyst; the methane conversion, CO2 conversion and H-2 selectivity increased while the H-2/CO ratio decreased markedly with increasing reaction temperature. While the O-2/CH4 ratio did not strongly affect the CH4 and CO2 conversion and H-2 selectivity, it had an intense influence on the H-2/CO ratio. The CH4 and CO2 conversion and the H-2 selectivity decreased while the H-2/CO increased with increasing space velocity. The O-2/CH4 ratio and the reaction temperature could be used to manipulate the heat of the reaction for the OCRM process. Depending on the O-2/CH4 ratio and temperature the OCRM process could be operated in a mildly exothermic, thermal neutral or mildly endothermic mode. The OCRM reaction became almost thermoneutral at an OCRM reaction temperature of 850 degrees C, O-2/CH4 ratio of 0.45 and space velocity of 46,000 cc/g/h. The CH4 conversion and H-2 selectivity over the CoO/MgO/SA-5205 catalyst corresponding to thermoneutral conditions were excellent: 95% and 97%, respectively with a H-2/CO ratio of 1.8. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: methane; oxy-CO2 reforming; Syngas

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Propane conversion to aromatics on highly active H-GaAlMFI: effect of thermal pretreatment - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Energy & Fuel, 2006)
The propane aromatization activity over H-GaAlMFI has been investigated after different thermal pretreatments ( calcination temperature range: 500- 800 degrees C) at a reaction temperature of 500 degrees C and in the space velocity range of 1500-12000 cm(3)/g/h. The calcination temperature had a strong influence on the strong acidity of the zeolite, propane conversion, and aromatic distribution. The decrease in acidity with increased thermal treatment severity correlated well with the decrease in the framework Ga. There was a considerable decrease in propane aromatization activity at calcination temperatures above 600 degrees C. The effect of calcination temperature on the propane aromatization activity can be explained in terms of change in the strong acidity of the zeolite and the extraframework Ga content. The selectivity for aromatics was found to decrease with increasing thermal pretreatment severity, while that for methane, ethane, and propylene was found to increase. The aromatic distribution was also influenced by the thermal pretreatment; the selectivity for benzene increased with increasing pretreatment temperature, while the selectivity for toluene, C-8 aromatics, and C9+ aromatics decreased.

CO2 reforming of methane to syngas over highly active and stable supported CoOx (accompanied with MgO, ZrO2 or CeO2) catalysts - Mondal, Kartick C.; Choudhary, Vasant R.; Joshi, Upendra A. (Applied Catalysis A-General, 2007)
{Catalytically inactive CoOx-MgO (calcined at 900 degrees C) becomes highly active and selective in the CO2 reforming of methane to syngas when it is deposited on a commercial low surface-area macro-porous silica-alumina support (SA-5205) or when CoOx is deposited on the support precoated with MgO. Both the supported CoOx and MgO containing catalysts (CoOx -MgO/SA-5205 and CoOx/MgO/SA-5205) show high methane conversion (> 98%) activity and H-2 selectivity (> 94%) and also high stability against carbon deposition [
Keywords: arylboronic acids; diarylmethylidenefluorene; dibromomethylidenefluorene; Pd-mediated coupling; Suzuki reaction

Decomposition and/or hydrogenation of hydrogen peroxide over Pd/Al2O3 catalyst in aqueous medium: factors affecting the rate of H2O2 destruction in presence of hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Hydrogen peroxide destruction by its decomposition and/or hydrogenation to water in the presence of H-2 over Pd(5 wt.%)/Al2O3 catalyst in an aqueous reaction medium, similar to that used in the H-2-to-H2O2 oxidation, has been thoroughly investigated at different reaction conditions. The H2O2 destruction is strongly influenced by the oxidation state of Pd in the catalyst and also by the presence of different halide anions (viz. F-, Cl-, Br- and I-) in the acidic aqueous medium or in the catalyst, depending upon the concentration of halide anions. The cations associated with halide anions have, however, a little or no influence on the H2O2 destruction. The iodide anions strongly poisoned the catalyst, even at their very low concentration. The fluoride anions have only a small effect on the H2O2 destruction. The chloride or bromide anions drastically inhibit the rapid H2O2 decomposition, but promote the slower H2O2 hydrogenation. The H2O2 destruction reactions are strongly influenced by the halide anion and acid concentrations. The presence of acid (protons) plays a very important role in drastically reducing the H2O2 destruction, particularly in the presence of chloride anions. Both in the presence and absence of Cl- or Br- anions, the H2O2 destruction activity of the catalyst is markedly reduced because of the oxidation of Pd but it is drastically increased due to the presence of H-2. A plausible reaction mechanism for the rapid H2O2 decomposition and slower H2O2 hydrogenation reactions, prevailing under the different reaction conditions, has also been discussed. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: decomposition of H2O2; halide anions as catalyst promoter or indicator; Hydrogen peroxide; hydrogenation of H2O2; Pd/Al2O3

Direct formation of H2O2 from H-2 and O-2 and decomposition/hydrogenation of H2O2 in aqueous acidic reaction medium over halide-containing Pd/SiO2 catalytic system - Samanta, Chanchal; Choudhary, Vasant R. (Catalysis Communications, 2007)
Formation of H2O2 from H-2 and O-2 and decomposition/hydrogenation of H2O2 have been studied in aqueous acidic medium over Pd/SiO2 catalyst in presence of different halide ions (viz. F-, Cl- and Br-). The halide ions were introduced in the catalytic system via incorporating them in the catalyst or by adding into the reaction medium. The nature of the halide ions present in the catalytic system showed profound influence on the H2O2 formation selectivity in the H-2 to H2O2 oxidation over the catalyst. The H2O2 destruction via catalytic decomposition and by hydrogenation (in presence of hydrogen) was also found to be strongly dependent upon the nature of the halide ions present in the catalytic system. Among the different halides, Br- was found to selectivity promote the conversion of H-2 to H2O2 by significantly reducing the H2O2 decomposition and hydrogenation over the catalyst. The other halides, on the other hand, showed a negative influence on the H2O2 formation by promoting the H-2 combustion to water and/or by increasing the rate of decomposition/hydrogenation of H2O2 over the catalyst. An optimum concentration of Br- ions in the reaction medium or in the catalyst was found to be crucial for obtaining the higher H2O2, yield in the direct synthesis. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Br- catalyst promoter; direct H2O2 formation; H2O2 decomposition; Pd/SiO2 catalyst

Direct oxidation of H-2 to H2O2 over Br and F-promoted Pd/Al2O3 in aqueous acidic medium: influence of the concentration of Br and F and the method of incorporation of the two halogens in the catalyst on their beneficial synergetic effect on the net H2O2 - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2007)
Influence of the addition of F (0-1.1 mmol/g) in the pre-brominated Pd/Al2O3 (Br loading = 0.13 mmol/g) and also that of Br (0.13 mmol/g) in the pre-fluorinated Pd/Al2O3 (F loading = 0.53 mmol/g) on the net H2O2 formation in the H-2-to-H2O2 oxidation (with H-2/O-2 mole ratio of 1.0) over the halogenated catalysts in aqueous acidic (0.1 M H3PO4) medium have been investigated. In both the cases, the highest synergetic effect (resulting in the highest net H2O2 formation) produced by the addition of other halogen is observed at its optimum concentration (viz. 0.13 mmol Br/g in the fluorinated Pd/Al2O3 and 0.13 mmol F/g in the pre-brominated Pd/Al2O3). The beneficial synergetic effect of the two halogens is also found to be strongly influenced by the way of incorporation of the two halogens in the catalyst. The enhancement in the net rate of H2O2 formation due to the synergetic effect for the different methods of Pd/Al2O3 halogenation is in the following order: simultaneous bromination and fluorination < first fluorination and then bromination < first bromination and then fluorination. The fluorination (at optimum concentration of 0.13 mmol F/g) of the pre-brominated (0.13 mmol Br/g) Pd/Al2O3 led to the best catalyst for the H-2-to-H2O2 oxidation with 100% H-2 conversion and 78% H2O2 yield/selectivity. The destruction of H2O2 by its decomposition and/or hydrogenation over the halogenated catalysts has also been studied. (c) 2007 Published by Elsevier B.V.
Keywords: F and Br-promoted Pd/Al2O3; Hydrogen peroxide; oxidation of H-2-to-H2O2; synergetic effect of F and Br

Direct oxidation of hydrogen to hydrogen peroxide over Pd (or PdO)/Al2O3 in aqueous reaction medium: influence of different acids and halide anions in reaction medium on formation and destruction of H2O2 - Choudhary, Vasant R.; Ingole, Yugesh V.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Effects of different mineral acids (viz. H2SO4, H3PO4, HNO3, HCl, HBr, and HI), acid (H3PO4) concentration, different halide anions (viz. F-, Cl-, Br-, and I-), and halide anion concentration in aqueous reaction medium on the H2O2 formation (in H-2-to-H2O2 oxidation) and/or on the H2O2 destruction (by H2O2 decomposition and hydrogenation) activities of Pd (or PdO)/Al2O3 catalyst (at 300 K and atmospheric pressure) have been thoroughly investigated. Among the different halide anions, Br- anions are most effective for promoting the H2O2 formation and inhibiting the H2O2 destruction by both the H2O2 decomposition and/or hydrogenation. The cations associated with the halide anions, however, have only a little or no influence on both the H2O2 formation and destruction. The concentration of the different halide anions has a strong influence on the H-2 conversion and H2O2 formation and destruction activities of the Pd/Al2O3. The H2O2 formation activity in the presence of Br- or Cl- anions is highest at the optimum concentration of halide (about 1.0 mmol/dm(3)). it is also highest at the optimum concentration of phosphoric acid (between 0.1 and 0.3 mol/dm(3)). In general, the H2O2 formation is increased with decreasing the H2O2 destruction activity of the catalyst, indicating a close relationship between the two. Br- anions act as an excellent catalyst promoter for Pd/Al2O3 catalyst, but they show only a small promoting effect for PdO/Al2O3 catalyst. The next choice for halide promoter for Pd/Al2O3 catalyst is Cl- anions. F- and I- anions are, however, catalyst inhibitor and strong poison, respectively, for the H2O2 formation. At the same concentration, Br- anions are more effective than Cl- anions for inhibiting the H2O2 destruction reactions over Pd/Al2O3 Catalyst. For both halide promoters (Cl- and Br-), the net H2O2 formation is controlled by the H2O2 hydrogenation rather than by the H2O2 decomposition.

Direct synthesis of H2O2 from H-2 and O-2 over Pd/H-beta catalyst in an aqueous acidic medium: influence of halide ions present in the catalyst or reaction medium on H2O2 formation - Samanta, Chanchal; Choudhary, Vasant R. (Catalysis Communications, 2007)
The influence of different halide ions present in the catalyst or reaction medium on the performance of Pd/H-beta catalyst in the direct H2O2 synthesis in an aqueous acidic (0.03 M H3PO4) reaction medium at 27 degrees C and atmospheric pressure has been thoroughly investigated. The results showed a strong influence of both the bulk Pd oxidation state in the catalyst and the halide ions added to the reaction medium on the performance of the catalyst in the H-2 to H2O2 oxidation, H2O2 decomposition/hydrogenation reactions. The different ammonium halides impregnated reduced Pd/H-beta catalyst calcined in inert (N-2) and oxidizing (air) gaseous atmospheres also revealed that the bulk Pd oxidation state and nature of the halide ions present in the catalyst together control the overall performance of the catalyst in the H2O2 formation reaction. The presence of halide ions in reaction medium or in the catalyst significantly changes the selectivity for H2O2 formation in the direct H2O2 synthesis. Bromide ions are found to remarkably enhance the H2O2 selectivity in the direct H2O2 synthesis irrespective of the Pd oxidation state in the catalyst. The promoting action of Br- is attributed mainly to the large decrease in the H2O2 decomposition and hydrogenation activities of the catalyst and also inhibition for the non-selective H-2-to-water oxidation over the catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H-P supported Pd catalyst; H2O2 decomposition; H2O2 hydrogenation; promoting action of bromide ions

Direct synthesis of H2O2 from H-2 andO(2) and decomposition/hydrogenation of H2O2 in an aqueous acidic medium over halide-modified Pd/Al(2)O3 catalysts - Samanta, Chanchal; Choudhary, Vasant R. (Applied Catalysis A-General, 2007)
Direct synthesis Of H2O2 from its elements was carried out in an acidic aqueous reaction medium over halide-modified oxidized and reduced Pd/ Al2O3 catalysts under very mild conditions (at 27 degrees C and atmospheric pressure). The halide ions were introduced into the catalyst by incorporating halide ions into supported Pd/gamma-Al2O3 catalyst or via depositing halide ions on the support (gamma-Al2O3) prior to Pd deposition. The H2O2 decomposition and hydrogenation over the corresponding catalysts were also carried out under the reaction conditions similar to those employed for the H2O2 synthesis in order to elucidate the factors strongly affecting the H2O2 yield/selectivity in the direct H2O2 process. The performance of halide-modified Pd/Al2O3 catalysts in the direct H2O2 synthesis revealed that halide insertion in the catalyst system prior to or after Pd deposition on the support had comparable qualitative effect on the H2O2 formation. Both the Pd oxidation state and the nature of the halide ions had strong influences on the H-2 conversion (in direct H2O2 Synthesis process) and H2O2 decomposition and/or hydrogenation reaction. While the effect of Pd oxidation state on the H2O2 formation was significant for the catalytic system containing F- and Cl- ions, the influence of the Pd oxidation state was found less important for the catalyst system containing Br- ions; the H2O2 formation selectivity increased significantly due to the presence of Br- ions, irrespective of the Pd oxidation state. The nature of the H2O2 destruction pathway (i.e. hydrogenation and/or decomposition) in the presence of hydrogen over halide-modified Pd/Al2O3 catalysts was found to be strongly dependent upon the nature of the halide ions incorporated in the catalyst during halide-modification of the catalyst. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H2O2 decomposition; H2O2 hydrogenation; halide-modification; Pd oxidation state

Formation from direct oxidation of H-2 and destruction by decomposition/hydrogenation of H2O2 over Pd/C catalyst in aqueous medium containing different acids and halide anions - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Applied Catalysis A-General, 2007)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 (at 27 degrees C and atmospheric pressure) over Pd/C catalyst in an aqueous acidic reaction medium have been thoroughly investigated using different mineral acids (viz. 0.1 N H2SO4, H3PO4, H3BO3, HNO3, HCl, HBr or HI) and/or halide anions (viz. F-, Cl-, Br- or I-), covering their wide concentration range (0-24 mmol/dm(3)), in the reaction medium. In the absence of any externally added halide, appreciable H2O2 formation in the H2 oxidation occurred only when the medium contained HCl. However, the rates of H2O2 decomposition and hydrogenation are greatly reduced because of the presence of any acid; the influence on the H2O2 decomposition was, however, much larger for the halo acids. In the presence of acid (0.1 N H3PO4 or H2SO4), the H-2-to-H2O2 formation reaction is greatly enhanced by the externally added halide anions up to their optimum concentrations. However, above the optimum halide anion concentration, it is inhibited more than the H-2-to-water formation (parallel) reaction, causing a decrease in both the H2O2 yield and selectivity. Whereas, the H-2 conversion and H2O2 destruction activities of the catalyst are decreased continuously with increasing the halide anion (except F-) concentration. Among the halides, chloride is the best halide promoter for Pd/C catalyst in the H-2-to-H2O2 oxidation. At the optimum Cl-concentration (5.4 mmol/dm(3)), both the H-2 conversion and H2O2 yield are passed through a maximum and the H2O2 decomposition is greatly inhibited with increasing the phosphoric acid concentration. In the absence of either the chloride anions or the acid (or both) in the reaction medium, only a little or no H2O2 is formed in the H-2 oxidation and also the rate of H2O2 destruction is very fast, particularly in the presence of H-2; the rapid destruction of H2O2 is mainly due to its decomposition rather than its hydrogenation. The best H-2-to-H2O2 oxidation results are obtained at the optimum concentrations of both the acid and halide anions. In the presence of acid and chloride (or bromide) promoter, the H2O2 hydrogenation dominates the H2O2 destruction and hence the net H2O2 formation is mainly controlled by the H2O2 hydrogenation. (c) 2006 Published by Elsevier B.V.
Keywords: H2O2 decomposition; H2O2 hydrogenation; halide anion promoters; Hydrogen peroxide; oxidation of H-2-to-H2O2; Pd/C catalyst

GaClx- or GaAlClx-grafted Si-MCM-41: highly active and moisture insensitive/stable catalyst for the acylation and benzylation of benzene, naphthalene and substituted benzenes - Choudhary, Vasant R.; Jha, Rani (Applied Catalysis A-General, 2007)
GaClx- and GaAlClx-grafted Si-MCM-41 catalysts were prepared by reacting anhydrous GaCl3 and mixed anhydrous GaCl3 and AlCl3, respectively, with the terminal hydroxyl groups of Si-MCM-41 (pore size: 2.5 nm) in a dry non-aqueous reaction medium (CCl4) under reflux. The catalysts showed high activity for both the acylation and benzylation (with benzoyl chloride and benzyl chloride, respectively) of benzene, toluene, p-xylene, cumene, mesitylene, anisole and naphthalene. Both the catalysts are moisture insensitive or less moisture sensitive; the presence of moisture has a beneficial effect in the acylation over both the catalysts. The catalytically active sites of the GaClx-grafted Si-MCM-41 are (-O-)(2)GaCl (i.e. partially chlorided Ga anchored to Si through -O- linkage) species and the equivalent sites of the GaAlClx-grafted Si-MCM-41 are (-O-)(2)Ga(or Al)Cl and (-O-)(3)Ga(or Al) species. The high acylation/benzylation activities of both the catalysts even in the presence of moisture are attributed to their redox properties (Ga3+ -> Ga1+) rather than to their Lewis acid properties. After the grafting/chemical bonding, the grafted gallium chloride catalyst showed much higher acylation activity but lower benzylation activity than the physically deposited (on Si-MCM-41) or unsupported GaCl3. The GaAlClx-grafted Si-MCM-41 showed higher acylation activity than the GaClx-grafted Si-MCM-41, due to a synergetic effect of the Ga and Al species. However, the relative benzylation activity of the two catalysts showed strong dependence upon the presence or absence of electron donating group(s) and also upon the electron donating ability of the group(s) attached to the aromatic nucleus. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: acylation benzylation; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; moisture insensitive

Generation of hydrogen peroxide via the selective reduction of oxygen by hydrazine sulfate over Br-promoted Pd/Al2O3 catalyst in an aqueous medium at ambient conditions - Choudhary, Vasant R.; Jana, Prabhas; Samanta, Chanchal (Applied Catalysis A-General, 2007)
The in situ generation of H2O2 via the selective reduction of OZ by hydrazine sulfate (in an aqueous medium) has been thoroughly investigated over the Br-promoted Pd(or PdO)/Al2O3 catalyst. The influence of the following factors have been addressed in this study: (a) Br concentration (in the reaction medium or incorporated in the catalyst); (b) reaction conditions (viz. reaction time, temperature); (c) concentrations of reducing agent and phosphoric acid in the reaction medium. Decomposition of N2H4 (from NH4-H2SO4) and its reaction with H2O2 under similar reaction conditions (in the absence of O-2) have also been studied. H2O2, which is an intermediate product of the O-2 reduction, is involved in further consecutive reactions. It can be converted to water via its decomposition and/or reaction with the unconverted NZH(4). In the presence of Br promoter, the later (reaction with unconverted N2H4) is more dominant. Both the consecutive reactions are drastically retarded in the presence of protons and Br promoter. A plausible reaction mechanism has been proposed for illustrating the role of the protons and Br promoter in the selective formation of H2O2 in the O-2 reduction process. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: brominated Pd/Al2O3 catalyst; hydrazine sulfate; Hydrogen peroxide; in situ H2O2 generation; oxygen reduction; Pd/Al2O3 catalyst

Hydrogenation of hydrogen peroxide over palladium/carbon in aqueous acidic medium containing different halide anions under static/flowing hydrogen - Choudhary, Vasant R.; Samanta, Chanchal; Jana, Prabhas (Industrial & Engineering Chemistry Research, 2007)
Kinetics of the hydrogenation of hydrogen peroxide (at 278 and/or 300 K) over Pd(5 wt%)/carbon in aqueous medium with or without containing acid or different halide anions (F-, Cl-, Br-, or I-) under static H-2 (i.e. batchwise) or flowing H-2 (i.e. semi-batchwise) at atmospheric pressure have been thoroughly studied. In the absence of protons or halide anions and also in the presence of F- anions, a very rapid decomposition of H2O2 (H2O2 -> H2O + 0.5O(2)) predominates over the H2O2 hydrogenation (H2O2 + H-2 -> 2H(2)O). However, in the presence of both the protons and Cl- or Br- anions, the H2O2 conversion occurs mainly by the hydrogenation reaction. The hydrogenation is found to be a zero-order reaction with respect to the H2O2 concentration, and its activation energy and frequency factor are strongly influenced by the halide anions. The hydrogenation is found to be more and more inhibited with increasing halide (Cl- or Br-) anion concentration. The cations associated with the halide anions have, however, only a very little influence on the hydrogenation. Iodide anions act as a very strong catalyst poison for the hydrogenation. In the presence of acid, the hydrogenation is very strongly influenced by the different halides, but, in the presence of halide anions (5.4 mmol/dm(3)), it is very mildly influenced by the different mineral acids (except HI). In the absence of protons, the Cl- and Br- anions are ineffective for inhibiting the rapid H2O2 decomposition. A role played by protons and halide anions for drastically inhibiting the rapid H2O2 decomposition is discussed.

In situ generation of hydrogen peroxide from reaction of O-2 with hydroxylamine from hydroxylammonium salt in neutral aqueous or non-aqueous medium using reusable Pd/Al2O3 catalyst - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2007)
In situ generation of H2O2 with high yield can be accomplished by reacting 02 with NH2OH from hydroxylammonium salt [NH2OH.HCl or (NH2OH)(2) . H2SO4] in a neutral aqueous medium using a reusable heterogeneous Pd (1.0 wt%)/Al2O3 catalyst, even at low temperature (10 degrees C), with the formation of harmless by-products (viz. N-2 and water). The presence of KCl or KBr in the medium has beneficial effect. The H2O2 generation is strongly influenced by the pH of medium, reaction period and temperature; best results are obtained at the optimum pH and reaction medium. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Hydrogen peroxide; hydroxylamine; Hydroxylammonium salt; in situ H2O2 generation; oxygen; Pd/AlO3 catalyst

Oxy-methane reforming over high temperature stable NiCoMgCeOx and NiCoMgOx supported on zirconia-haffnia catalysts: accelerated sulfur deactivation and regeneration - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Catalysis Communications, 2007)
NiCoMgOx and NiCoMgCeOx on commercial low surface area zirconia-haffnia catalysts have unusually high thermal stability (>= 2000 degrees C) for syngas generation via the methane partial oxidation process (J. Catal., 233, 36, 2005). Herein we report the results on accelerated sulfur deactivation (0.74 mol% sulfur in feed) and corresponding regeneration (at 800 degrees C in 1:1 O-2 + N-2 flow) over these catalysts. The NiCoMgCeOx catalyst, due to a larger mobility of lattice oxygen, showed a considerably higher resistance to sulfur poisoning; the higher mobility of the lattice oxygen in case of the NiCoMgCeOx catalyst may be related to the presence of CeO2. During the deactivation process, the selectivity for H-2 was decreased to a much greater extent than that for CO. Regeneration studies showed that even after complete deactivation of the catalysts, the original activity/selectivity of both the catalysts could be completely restored after a simple regeneration process. Based on their exceptionally high thermal stability, high activity/selectivity and easily regenerability, the NiCoMOx, and NiCoMgCeOx catalysts appear to be very promising candidates for the CPOM process. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Deactivation; high temperature stable; methane; Partial oxidation; Regeneration; Sulfur

Reduction of oxygen by hydroxylammonium salt or hydroxylamine over supported Au nanoparticles for in situ generation of hydrogen peroxide in aqueous or non-aqueous medium - Choudhary, Vasant R.; Jana, Prabhas; Bhargava, Suresh Kumar (Catalysis Communications, 2007)
Reaction of O-2 with hydroxylamine or its salts over a number of supported gold catalysts containing An nanoparticles (at 10-70 degrees C) has been studied at atmospheric pressure for the in situ generation of H2O2 (required for organic oxidation reactions in the synthesis of fine/specialty chemicals) in aqueous (water) or non-aqueous medium. Hydrogen peroxide in high yields with harmless by-products (viz. water and nitrogen) can be generated in situ by the reduction Of O-2 by hydroxylammonium sulfate (or chloride) or hydroxylamine using the supported gold catalysts particularly Au/Gd2O3, Au/La2O3 and Au/MgO, in aqueous (water) or non-aqueous (viz. methanol) medium at close to ambient conditions. The reduction of O-2 by hydroxylammonium salt to H2O2, however, requires preneutralization of the salt by alkali; in the absence of the neutralization, only water is formed in the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Au Nanoparticles; Au/Gd2O3; Au/La2O3; Au/MgO; Hydrogen peroxide; hydroxylamine; hydroxylammonium salts; in situ H2O2 generation

Solvent-free selective oxidation of benzyl alcohol by molecular oxygen over uranium oxide supported nano-gold catalyst for the production of chlorine-free benzaldehyde - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Green Chemistry, 2007)
A detailed investigation on the production of chlorine-free benzaldehyde in the solvent-free oxidation of benzyl alcohol by O-2 over nano-gold supported on U3O8 has been carried out. Influence of different catalyst parameters (different methods of gold deposition on U3O8, gold loading and particle size, and catalyst calcination temperature) and reaction conditions (reaction period and temperature) on the process performance has been studied. The catalyst containing gold at higher concentration and with smaller gold particles showed the better process performance (higher benzyl alcohol conversion and benzaldehyde yield or selectivity). The benzyl alcohol conversion is largely increased but the selectivity for benzaldehyde is slightly decreased (while that of benzyl benzoate is increased) with increasing the reaction period or temperature. In the presence of solvent (viz. tolune, p-xylene, DMF or DMSO), the process performance was found to be inferior to that observed in the absence of any solvent. Substituted benzyl alcohols also can be oxidized by O-2 to corresponding aldehydes with high yield and/or selectivity, using the catalyst in the absence of any solvent.

Supported copper oxide as a highly active/selective catalyst for the epoxidation of styrene by TBHP to styrene oxide - Choudhary, Vasant R.; Jha, Rani; Chaudhari, Nitin K.; Jana, Prabhas (Catalysis Communications, 2007)
Liquid phase epoxidation of styrene by anhydrous and aqueous TBHP to styrene oxide has been studied under reflux, using different supported CuO (viz. Cuo/Si-MCM-41, CuO/Al2O3, CuO/Ga2O3 and CuO/In2O3) as easily separable and reusable heterogeneous catalysts. The CuO/Ga2O3 catalyst showed the best performance in the epoxidation by aqueous TBHP. The CuO supported on In2O3 or Si-MCM-41 also showed very good performance in the epoxidation but only by anhydrous TBHP. However, the CUO/SiO2 catalyst, however, showed very good performance in the epoxidation by both the anhydrous and aqueous TBHP. Influence of the reaction conditions (temperature, time and TBHP/styrene ratio) on the epoxidation by aqueous TBHP over the best catalyst (CuO/Ga2O3) has been investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CuO/Al2O3; CuO/Ga2O3; CuO/In2O3; Cuo/Si-MCM-41; CuO/SiO2; epoxidation; styrene; Styrene oxide; tertiary butyl hydroperoxide

Synergetic effect of two halogen promoters present in acidic reaction medium or catalyst on the H2O2 formation (in H-2-to-H2O2 oxidation) and destruction over Pd/C (or Al2O3) catalyst - Choudhary, Vasant R.; Jana, Prabhas (Journal of Catalysis, 2007)
A strong synergetic effect of two different halide anions (F- and I-, Cl- and I-, Cl- and Br-, and F- and Br-) at optimum concentration in the catalyst or in an acidic reaction medium was observed in the H-2-to-H2O2 oxidation over Pd/C, Pd/Al2O3, and halogenated Pd/Al2O3 catalysts. The synergetic effect promote, the net H2O2 formation by inhibiting the H2O2 decomposition and hydrogenation reactions. The effect is most pronounced for the combination of fluoride (or chloride) and iodide anions. The Br (1 wt%)-F (1 wt%)-Pd (5 wt%)/Al2O3 catalyst showed very high H2O2 yield (59%)/selectivity (60%) in the H-2-to-H2O2 oxidation. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: H-2-to-H2O2 oxidation; H2O2 decomposition H2O2 hydrogenation; halogen promoter; Hydrogen peroxide; Pd/Al2O3; Pd/C; synergetic effect

Direct H(2)-to-H(2)O(2) oxidation in aqueous acidic medium containing Br promoter over Pd/Al(2)O(3) and Pd/C catalysts thermally pretreated under different conditions - Choudhary, Vasant R.; Jana, Prabhas; Bhargava, Suresh Kumar (Catalysis Letters, 2008)
Influence of thermal pretreatments (under N(2), air or H(2) gas atmosphere at 500 degrees C or 700 degrees C) has been investigated for the Pd/Al(2)O(3) and Pd/Carbon catalysts in terms of its effect on their Pd particle size and performance in the H(2)-to-H(2)O(2) oxidation and H(2)O(2) destruction (by decomposition and/or hydrogenation) reactions in aqueous acidic medium containing Br promoter. The influence on the net H(2)O(2) formation is found to depend strongly upon the catalyst support due to support-Pd cluster interactions. For both the catalysts, the thermal treatments (except in air) caused a large increase in their Pd particle size. The increase in Pd particle size caused an increase in the H(2)O(2) formation activity of Pd/Al(2)O(3) but a decrease in the H(2)O(2) formation activity of Pd/C.
Keywords: Hydrogen peroxide; oxidation of H(2) to H(2)O(2); Pd/Al(2)O(3); Pd/C

Direct oxidation of H-2 to H2O2 over different supported PdO catalysts in aqueous acidic medium: Influence of the reduction, calcination temperature and support of the catalyst on its net H2O2 formation activity - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the catalyst reduction (by hydrazine), calcination temperature (400-800 degrees C) and support (viz. Al2O3, SiO2, CeO2, ZrO2, HP or HM) on the performance of supported PdO (2.5 wt%) catalyst in the H-2-to-H2O2 oxidation (with H-2:O-2 = 1: 1) in an aqueous acidic (0.1 M H3PO4) medium under ambient conditions have been investigated. All the supported PdO catalysts showed lower H2 conversion activity, but higher H2O2 selectivity, as compared to their reduced counter parts. The catalyst performance for the net H2O2 formation is strongly influenced by both the support and calcination temperature of the supported PdO catalysts. The catalysts calcined at 400 degrees C showed better performance. Among the catalysts, PdO/Al2O3 catalyst (calcined at 400 degrees C) showed the best performance (17.0% H2O2 yield) in the H-2-to-H2O2 oxidation. The influence of the calcination temperature of PdO/Al2O3 catalyst on its H2O2 decomposition and hydrogenation activities has also been investigated. Both the H2O2 decomposition and hydrogenation activities increased with increasing the calcination temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrogen peroxide; oxidation of H-2 to H2O2; supported PdO catalysts

Direct oxidation of H-2 to H2O2 over Pd/CeO2 catalyst under ambient conditions: influence of halide ions - Samanta, Chanchal; Choudhary, Vasant R. (Chemical Engineering Journal, 2008)
Direct oxidation of H-2 by O-2 to H2O2 and decomposition/hydrogenation of H2O2 have been investigated over Pd/CeO2 catalyst in presence of different halide ions. All reactions were carried out in an aqueous acidic (0.03 M H3PO4) medium at room temperature (25 degrees C) and atmospheric pressure. When different halide ions were added directly to the reaction medium or incorporated in the catalyst, the activity/selectivity of Pd/CeO2 catalyst in the H-2 to H2O2 oxidation changed significantly, depending upon the nature of the halide ions. Different ammonium halides impregnated reduced Pd/CeO2 catalyst calcined under inert (flowing nitrogen) and oxidizing (static/flowing air) gaseous atmospheres revealed that bulk oxidation state of Pd and the nature of the halide ions incorporated into the catalyst cooperatively control the activity/selectivity of catalyst in H-2 to H2O2 oxidation. Both H2O2 decomposition and hydrogenation were found to affect strongly depending upon the nature of the halide ions present in the reaction medium or in the catalyst. Among the different halides, bromide was found the most effective promoter for enhancing the H2O2 yield/selectivity in H-2 to H2O2 oxidation, irrespective of the Pd oxidation state in the catalyst. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Br- ions; H-2 to H2O2 oxidation; H2O2 decomposition; H2O2 hydrogenation; Pd/CeO2 catalyst

Direct oxidation of H-2 to H2O2 over PdO/Al2O3 catalysts in aqueous acidic medium: influence on H2O2 formation of Pd loading, calcination temperature and reduction of catalyst and presence of halide anions - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the Pd loading (0.2-10 wt%), calcination temperature (400-900 degrees C) and reduction of PdO/Al2O3 on its performance in the H-2-to-H2O2 oxidation (with H-2/O-2 = 1:1) in an aqueous 0.1 M H3PO4 medium, in the absence and presence of different halide anions, under ambient conditions have been investigated. The effect of calcination temperature on the H2O2 formation varied depending upon the Pd loading. The influence of the different halide anions was found to depend strongly on the nature of halide anion (F-, Cl-, Br- or I-) and the oxidation state of Pd and its loading in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: halide catalyst promoters; Hydrogen peroxide; oxidation of H-2 to H2O2; Pd/Al2O3; PdO/Al2O3

Energy-efficient syngas production through, catalytic oxy-methane reforming reactions - Choudhary, Tushar V.; Choudhary, Vasant R. (Angewandte Chemie-International Edition, 2008)
Keywords: fuels; heterogeneous catalysis; methane activation; Partial oxidation; Syngas

Factors influencing the in situ generation of hydrogen peroxide from the reduction of oxygen by hydroxylamine from hydroxylammonium sulfate over Pd/alumina - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2008)
Influence of the concentration of bromide (KBr) promoter, reaction period, temperature, catalyst loading and initial concentration of hydroxylammonium sulfate on the formation of H2O2 due to the reaction between hydroxylamine from the hydroxylammonium salt and molecular oxygen over Pd (1 wt%)/Al2O3 catalyst in a neutral aqueous medium at close to the ambient conditions has been investigated. Effect of pH and temperature on the destruction of H2O2, Occurring in the consecutive reactions, over the catalyst in the presence or absence of bromide promoter and hydroxylamine has also been studied. In the absence of O-2, the conversion of hydroxylamine by its decomposition over the catalyst increases sharply with increasing the pH, particularly above the pH of 7.0; at or below the pH of 7.0, it is quite small. The H2O2 destruction increases markedly with increasing the pH of medium and reaction temperature but it is found to decrease in the presence of hydroxylamine. For the highest net H2O2 formation, not only the optimum pH (7.0) of reaction medium but also the optimum other reaction conditions (viz. bromide promoter concentration, reaction period, temperature or catalyst loading) are necessary. The reaction path and mechanism for the generation of H2O2 have also been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: H2O2 destruction; Hydrogen peroxide; hydroxylamine; Hydroxylammonium sulfate; Pd/Al2O3 catalyst; reduction of O-2

GaAlCl(x)-grafted Mont.K-10 clay: highly active and stable solid catalyst for the friedel-crafts type benzylation and acylation reactions - Choudhary, Vasant R.; Jha, Rani (Catalysis Communications, 2008)
A liquid phase reaction of anhydrous GaCl(3) and AlCl(3) with the surface hydroxyl groups (with HCl evolution) of Mont. K-10 clay in dry CCL(4) under reflux resulted in a novel GaAlCl(x),-grafted Mont.K-10 catalyst [with Cl/(Ga + Al) = 1]. The catalyst showed high activity and stability in the Freidel-Crafts type benzylation and benzoylation (by benzyl chloride and benzoyl chloride, respectively) of benzene, naphthalene and substituted benzenes, even in the presence of moisture. It also showed good activity for the benzoylation of nitrobenzene (i.e. even in the presence of strong electron withdrawing group, like nitro group, attached to the benzene ring). The catalytically active surface species in the catalyst are -(O)(2)-Ga(or Al)Cl. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: benzoylation of aromatics; benzylation of aromatics; GaAlCl(x)-grafted Mont.K-10

Influence of alkali metal doping on surface properties and catalytic activity/selectivity of CaO catalysts in oxidative coupling of methane - Rane, V. H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2008)
Surface properties viz. surface area, basicity/base strength distribution, and crystal phases) of alkali metal doped CaO (alkali metal/Ca = 0.1 and 0.4) catalysts and their catalytic activity/selectivity ill oxidative coupling of methane (OCM) to higher hydrocarbons at different reaction conditions (viz. temperature. 700 and 750 degrees C: CH(4)/O(2) ratio. 4.0 and 8.0 and space velocity. 5140-20550 cm(3). g(-1).h(-1)) have been investigated. The influence of catalyst calcination temperature on the activity/selectivity has also been investigated. The surface properties (viz. surface area, basicity/base strength distribution) and catalytic activity/selectivity of the alkali metal doped CaO Catalysts are strongly influenced by the alkali metal promoter and its concentration in the alkali metal doped CaO catalysts. An addition of alkali Metal promoter to CaO results in a large decrease in the surface area but a large increase in the surface basicity (strong basic sites) and the C(2+) Selectivity and yield of the catalysts in the OCM process. The activity and selectivity are strongly influenced by the catalyst calcination temperature. No direct relationship between surface basicity and catalytic activity/selectivity has been observed. Among the alkali metal doped CaO catalysts. Na-CaO (Na/Ca = 0.1. before calcination) catalyst (calcined at 750 degrees C), showed best performance (C(2+) selectivity of 68.8% with 24.7% methane conversion), whereas (lie poorest performance was shown by the Rb-Cao Catalyst in the OCM process.
Keywords: alkali metal doped CaO catalysts; basicity/base strength distribution; catalytic activity/selectivity; oxidative coupling of methane

Nano-gold supported on Fe2O3: a highly active catalyst for low temperature oxidative destruction of methane green house gas from exhaust/waste gases - Choudhary, Vasant R.; Patil, V. P.; Jana, Prabhas; Uphade, B. S. (Applied Catalysis A-General, 2008)
A number of nano-gold catalysts were prepared by depositing gold on different metal oxides (viz. Fe2O3, Al2O3, Co3O4, MnO2, CeO2, MgO, Ga2O3 and TiO2), using the homogeneous deposition precipitation (HDP) technique. The catalysts were evaluated for their performance in the combustion of methane (1 mol% in air) at different temperatures (300-600 degrees C) for a GHSV of 51,000 h(-1). The supported nano-gold catalysts have been characterized for their gold loading (by ICP) and gold particle size (by TEM/HRTEM or XRD peak broadening). Among these nano-gold catalysts, the Au/Fe2O3 (Au loading = 6.1% and Au particle size = 8.5 nm) showed excellent performance. For this catalyst, temperature required for half the methane combustion was 387 degrees C, which is lower than that required for Pd(1%)/Al2O3 (400 degrees C) and Pt(1%)/Al2O3 (500 degrees C) under identical conditions. A detailed investigation on the influence of space velocity (GHSV = 10,000-100,000 cm(3) g(-1) h(-1)) at different temperatures (200-600 degrees C) on the oxidative destruction of methane over the Au/Fe2O3 catalyst has also been carried out. The Au/Fe2O3 catalyst prepared by the HDP method showed much higher methane combustion activity than that prepared by the conventional deposition precipitation (DP) method. The XPS analysis showed the presence of Au in the different oxidation states (Au-0, Au1+ and Au3+) in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Au/Fe2O3; Deposition precipitation; Homogeneous deposition precipitation; Methane combustion; Supported nano-gold catalysts

Selective epoxidation of styrene to styrene oxide by TBHP using simple transition metal oxides (NiO, CoO or MoO3) as highly active environmentally-friendly catalyst - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Catalysis Communications, 2008)
Simple transition metal oxides, such as NiO, CoO or MoO3, etc. show high catalytic activity for the selective epoxidation of styrene to styrene oxide by TBHP. The order of choice for different transition metal oxides for epoxidation is NiO > CoO > MoO3 > Cr2O3 > Fe2O3 > ZnO >= U3O8 >> TiO2 >> MnO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CoO; epoxidation; MoO3; NiO; styrene; Styrene oxide; TBHP

Synthesis of substituted styrenes and stilbenes mediated by palladium on zirconia - Borate, Hanumant B.; Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Journal of Chemical Research-S, 2008)
Palladium on zirconia has been found to be an effective catalyst for the synthesis of various substituted styrenes and stilbenes, including biologically active natural products, by reaction of aryl halides with olefins.
Keywords: heterogeneous catalyst; palladium on zirconia; stilbenes; styrenes

Acylation of nitrobenzene and substituted nitrobenzenes by benzoyl chloride using GaClx- and GaAlClx-grafted meporous Si-MCM-41 catalysts - Choudhary, Vasant R.; Jha, Rani (Microporous and Mesoporous Materials, 2009)
A acylation of nitrobenzene and substituted nitrobenzene by benzoyl chloride can be accomplished with good yield in a short reaction period (<= 3 h), even in the presence of moisture, using GaClx- and GaAlClx-grafted mesoporous silica (Si-MCM-41) catalyst. The catalyst is reusable/environmentally friendly. The presence of moisture in the catalyst has beneficial effect on the acylation reaction. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Acylation; Benzoyl chloride; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; nitrobenzene

Direct H-2-to-H2O2 oxidation over highly active/selective Br-F-Pd/Al2O3 catalyst in aqueous acidic medium: Influence of process conditions on the H2O2 formation - Choudhary, Vasant R.; Jana, Prabhas (Applied Catalysis A-General, 2009)
The influence of the O-2/H-2 mote ratio in the gaseous feed and also those of other reaction conditions [viz. concentration of H3PO4 (0-5 mol/dm(3)). temperature (5-50 degrees C, gas (H-2 and O-2) space velocity (5.8-23.4 h(-1)) and reaction time (0.1-8 h)] on the H2O2 formation in the H-2-to-H2O2 oxidation over the Br(1 wt%)-F(1 wt%)-Pd(5 wt%)/Al2O3 catalyst in an aqueous acidic (H3PO4) medium have been thoroughly investigated. The effects of the O-2/H-2 ratio, reaction temperature and acid concentration on the destruction of H2O2 by its decomposition and/or hydrogenation reactions over the catalyst in the acidic reaction medium have also been studied. The net H2O2 formation (H2O2 yield) over the catalyst passed through a maximum with increasing the acid concentration, the temperature or the O-2/H-2 feed ratio. However, it decreased markedly with increasing the gas space velocity or the reaction period. The H2O2 decomposition and hydrogenation activities of the catalyst increased appreciably with increasing the reaction temperature and decreased with increasing the acid concentration. The H2O2 destruction during the H-2-to-H2O2 oxidation increased with increasing the concentration of H-2 (relative to that of O-2) due to the increased H2O2 hydrogenation rate over the catalyst. The net H2O2 formation in the H-2-to-H2O2 oxidation decreased sharply with increasing the initial amount of H2O2 present in the reaction mixture. The presence of H2O2 and the higher H-2/O-2 ratios have detrimental effects on the net formation of H2O2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Br-F-Pd/Al2O3 catalyst; H2O2 decomposition; H2O2 hydrogenation; hydrogen oxidation; Hydrogen peroxide

Magnesium oxide supported nano-gold: a highly active catalyst for solvent-free oxidation of benzyl alcohol to benzaldehyde by TBHP - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2009)
Nano-size gold particles deposited on MgO by the homogeneous deposition- precipitation showed very high catalytic activity with nearly 100% conversion of benzyl alcohol in a short reaction period (0.5 h) and more over showed excellent reusability in the process. Influence of the catalyst support (MgO, CaO, BaO, SrO, Al(2)O(3), Ga(2)O(3) and In(2)O(3)), method of gold deposition, Au loading and catalyst calcination temperature and also that of the reaction conditions (viz. reaction time and temperature) on the benzyl alcohol to benzaldehyde oxidation have been thoroughly investigated. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkaline earth oxides; Benzaldehyde; Benzyl alcohol; Gr.IIIa metal oxides; Oxidation

Oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over nanogold supported on TiO2 and other transition and rare-earth metal oxides - Choudhary, Vasant R.; Dumbre, Deepa K.; Bhargava, Suresh Kumar (Industrial & Engineering Chemistry Research, 2009)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide (at 95 degrees C) over nanogold supported oil TiO2 and other transition-metal oxides (viz, MnO2, Fe2O3, CoOx, NiO, CuO, ZnO, and ZrO2) or rare-earth oxides (viz, La2O3, Sm2O3, Eu2O3, and Yb2O3) by the homogeneous deposition-precipitation (HDP) method has been investigated. The Au/TiO2 catalyst, prepared using the HDP method, showed high activity and selectivity in the reaction. The ZrO2-Supported nanogold catalyst (HDP) also showed very good performance. The Au/TiO2 catalyst that was prepared using the deposition-precipitation (DP) method, however, showed poor catalytic activity, mostly because of its much-lower gold loading and/or lower Au3+/Au-0 ratio. Irrespective of the catalyst preparation method, the catalytic activity increased as the gold loading increased. The gold deposition method strongly influenced the amount of gold that was deposited on TiO2, the gold particle size distribution, and also the surface Au3+/Au-0 ratio; using the HDP method, the gold deposition was much larger, the gold particle size was smaller, the gold particle size distribution was much narrower, and the Au3+/Au-0 ratio was higher. Both the metallic and ionic gold species (Au-0 and Au3+) are present in the Au/TiO2 catalyst. However, the Au3+ species are mostly responsible for the high catalytic activity in the oxidation process.

Supported nano-gold catalysts for epoxidation of styrene and oxidation of benzyl alcohol to benzaldehyde - Choudhary, Vasant R.; Dumbre, Deepa K. (Topics in Catalysis, 2009)
Nano-gold particles supported on different alkaline earth oxides (viz. MgO, CaO, BaO and SrO), Gr. IIIa metal oxides (viz. Al(2)O(3), Ga(2)O(3), In(2)O(3) and Tl(2)O(3)), transition metal oxides (viz. TiO(2), Cr(2)O(3), MnO(2), Fe(2)O(3), CoO(x), NiO, CuO, ZnO, Y(2)O(3) and ZrO(2)), rare earth metal oxides (viz. La(2)O(3), Ce(2)O(3), Nd(2)O(3), Sm(2)O(3), Eu(2)O(3), Tb(2)O(3), Er(2)O(3) and Yb(2)O(3)) and U(3)O(8) [all prepared by depositing gold on corresponding metal oxide support by deposition precipitation (DP) and/or homogeneous deposition precipitation (HDP) method] were evaluated for their catalytic performance in the liquid phase epoxidation of styrene by tert-butyl hydroperoxide (TBHP) to styrene oxide and also in the solvent-free benzyl alcohol-to-benzaldehyde oxidation (by molecular oxygen or TBHP) reactions. For the epoxidation, the catalytic performance (styrene oxide yield) of the most promising nano-gold catalysts prepared by the HDP method was in the following order: Au/MgO > Au/Tl(2)O(3) > Au/Yb(2)O(3) > Au/Tb(2)O(3) > Au/CaO (or TiO(2)). However, for the oxidation of benzyl alcohol to benzaldehyde by molecular oxygen, the order of choice for the most promising catalysts (based on benzaldehyde yield) was Au/U(3)O(8) > Au/Al(2)O(3) > Au/ZrO(2) > Au/MgO. Whereas, when TBHP was used as an oxidizing agent for the benzyl alcohol oxidation, the order of choice for the most promising catalysts was Au/U(3)O(8) > Au/MgO > Au/TiO(2) > Au/ZrO(2) > Au/Al(2)O(3). The catalytic performance of a particular supported nano-gold catalyst was thus found to depend on the reaction catalysed by them. Moreover, it is strongly influenced by a number of catalyst parameters, such as the metal oxide support, the method of gold depositon on the support, the gold loading and also on the catalyst calcination temperature. Nano-gold particles-support interactions seem to play an important role in controlling the deposition of gold ( amount of gold deposited and size and morphology of gold particles), formation of different surface gold species (Au(0), Au(1+) and Au(3+)) and electronic properties of gold particles and, consequently, control the catalytic performance (both the activity and selectivity) of the supported nano-gold catalysts in the reactions. The nano-gold catalysts prepared by the HDP method showed much better catalytic performance than those prepared by the DP, coprecipitation or impregnation method; in general, the HDP method provided supported gold catalysts with much higher gold loading and/or smaller size gold particles than that achieved by the DP and other methods.
Keywords: Benzaldehyde; Benzyl alcohol; epoxidation; Metal oxide supports; Nano-gold catalysts; Oxidation; styrene; Styrene oxide

Oxidative coupling of methane over La-promoted CaO catalysts: influence of precursors and catalyst preparation method - Rane, Vilas H.; Chaudhari, Sopan T.; Choudhary, Vasant R. (Journal of Natural Gas Chemistry, 2010)
The oxidative coupling of methane to C(2) hydrocarbons has been studied over a series of La-promoted CaO (La/Ca = 0.05) catalysts, prepared using different precursor salts for CaO and La(2)O(3) (viz. acetates, carbonates, nitrates and hydroxides) and catalyst preparation methods (viz. physical mixing of precursors, co-precipitation using ammonium carbonate/sodium carbonate as a precipitating agent), under different reaction conditions (temperature: 700-850 degrees C, CH(4)/O(2) ratio: 4.0 and 8.0, and GHSV: 51360 cm(3).g(-1).h(-1)). The surface area and surface basicity/base strength distribution of the catalysts have also been investigated. The surface properties and catalytic activity/selectivity of the La-promoted CaO catalysts vary from catalyst to catalyst depending on the catalyst precursors used and catalyst preparation method. The basicity/base strength distribution is strongly influenced by the precursors (for CaO and La(2)O(3)) and catalyst preparation method. Basicity (total and strong basic sites measured in terms of CO(2) chemisorbed at 50 degrees C and 500 degrees C, respectively) observed for the catalyst prepared by co-precipitation method is higher than that of the catalysts prepared by physical mixing method. The catalysts prepared by the nitrates of La- and Ca- and co-precipitated by the solution of sodium carbonate and ammonium carbonate exhibit different catalytic performance in OCM. The finding that no direct relationship between the surface basicity and catalytic activity/selectivity in OCM exists indicates that basicity is not solely responsible for obtaining high selectivity to C(2) hydrocarbons.
Keywords: basicity distribution; La-promoted CaO catalysts; oxidative coupling of methane

Solvent-free selective oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over U3O8-supported nano-gold catalysts - Choudhary, Vasant R.; Dumbre, Deepa K. (Applied Catalysis A-General, 2010)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide over different uranium oxide supported nano-gold catalysts in the absence of a solvent has been thoroughly investigated. The influences of catalyst parameters [viz, method of gold deposition (impregnation, co-precipitation, deposition-precipitation and homogeneous deposition-precipitation), gold loading (08 wt%) and catalyst calcination temperature (100-900 degrees C)] on the catalyst performance have been investigated. The influence of reaction conditions [viz, reaction time (0-2 h) and temperature (25-94 degrees C)] on the process performance has also been studied. The Au/U3O8 catalyst prepared by the homogeneous deposition-precipitation and calcined at 400 degrees C showed very high activity (100% benzyl alcohol conversion with >85% selectivity for benzaldehyde) in the process for a short reaction period (0.5 h) at 94 degrees C. The catalyst also showed excellent reusability in the process. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Au/U3O8 catalyst; Benzaldehyde; Benzyl alcohol; Nano-gold; Partial oxidation; tert-Butyl hydroperoxide

Greener ullmann-type coupling of aryl halides for preparing biaryls using reusable Pd/ZrO2 catalyst - Dumbre, Deepa K.; Wakharkar, Radhika D.; Choudhary, Vasant R. (Synthetic Communications, 2011)
Biaryls with excellent yields can be prepared by the Ullmann-type coupling of aryl halides in the presence of potassium carbonate (as a base) and dimethylformamide (as a solvent), at 140 degrees C, using a reusable Pd (2.5wt%)/ZrO2 catalyst. The product yield of 4-iodoanisole coupling is strongly influenced by the catalyst preparation method, solvent, and base.
Keywords: Aryl halides; Biaryls; Pd; Ullmann coupling reaction; ZrO2

One-pot three-component kabachnik-fields synthesis of alpha-aminophosphonates using H-beta zeolite catalyst - Tillu, V. H.; Dumbre, Deepa K.; Wakharkar, R. D.; Choudhary, Vasant R. (Tetrahedron Letters, 2011)
One-pot three-component Kabachnik-Fields synthesis of alpha-aminophosphonates with high yields from the reaction between carbonyl compound, primary amine, and substituted phosphite can be carried out in a short period, using H-beta zeolite as a reusable catalyst. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carbonyl compound; H-beta zeolite; Primary amine; Substituted phosphite

Solvent-free selective oxidation of primary alcohols-to-aldehydes and aldehydes-to-carboxylic acids by molecular oxygen over MgO-supported nano-gold catalyst - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
Magnesium oxide supported nano-gold catalyst (prepared by the homogeneous deposition precipitation technique) showed high activity/selectivity and excellent reusability in the oxidation of different primary alcohols and aldehydes to corresponding aldehydes and carboxylic acids, respectively, by molecular oxygen (under atmospheric pressure) in the absence of any solvent. Influence of the catalyst calcination temperature (400-900 degrees C), reaction temperature (50-120 degrees C) and use of different solvents (viz. toluene. p-xylene, DMF or DMSO) on the oxidation reaction has also been studied. (C) 2011 Published by Elsevier B.V.
Keywords: Alcohols; aldehydes; Au/MgO; Molecular oxygen; Solvent-free oxidation

Thermally decomposed Ni-Fe-hydrotalcite: a highly active catalyst for the solvent-free N-acylation of different amines by acid chlorides - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2011)
A composite Ni-Fe catalyst obtained from the thermal decomposition of Ni-Fe-hydrotalcite at 600 degrees C shows very high activity in the solvent-free N-acylation of amines by different acid chlorides with high product yields under very mild reaction conditions (viz, room temperature, short reaction period and small amount of catalyst). The catalyst also shows excellent reusability in the reaction. The crystalline phases present in the catalyst are mixed oxides and hydroxides of nickel and iron. The high catalytic activity of the decomposed Ni-Fe-hydrotalcite is attributed to the formation of uniformly distributed Ni-Fe metal oxides and hydroxides. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Acid chlorides; amines; Decomposition of Ni-Fe-hydrotalcite; N-acylation of amines; Ni-Fe-hydrotalcite derived catalyst

FeCl3/Montmorillonite K10 as an efficient catalyst for solvent-free aza-Michael reaction between amine and alpha,beta-unsaturated compounds - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, S. K. (RSC Advances, 2012)
A highly efficient, inexpensive and greener protocol for aza-Michael addition reaction of different aromatic and aliphatic/cyclic amines to alpha,beta-unsaturated compounds using a FeCl3/MontK10 catalyst under solvent-free conditions has been developed. The Michael addition products are obtained in good to excellent yields. The catalyst was insensitive to moisture and it also showed excellent reusability in the reaction. Its high activity is attributed mostly to redox properties of FeCl3.

Solvent-free one-pot synthesis of sulfonephthaleins from saccharin and phenols - Tillu, V. H.; Dumbre, Deepa K.; Borate, Hanumant B.; Wakharkar, R. D.; Choudhary, Vasant R. (Synthetic Communications, 2012)
Sulfonephthaleins can be synthesized in a single pot from saccharin and phenol via the in situ formation of 2-sulfobenzoic anhydride, followed by its reaction with phenol using H2SO4 as the condensing agent, in the absence of any solvent. This solvent-free synthesis is more economical and environmentally benign.
Keywords: H2SO4; Phenols; saccharin; sulfonephthalein

Solvent-free oxidation of aldehydes to acids by TBHP using environmental-friendly -exchanged Mg-Al hydrotalcite catalyst - Choudhary, Vasant R.; Dumbre, Deepa K.; Narkhede, Vijay S. (Journal of Chemical Sciences, 2012)
A number of hydrotalcite (Mg-Al, Mn-Al, Co-Al, Ni-Al, Mg-Fe, Mg-Cr and Cu-Al) catalysts, with or without MnO-exchange, were evaluated for their performance in the solvent-free oxidation of benzaldehyde to benzoic acid by tert-butyl hydroperoxide under reflux in the absence of any solvent. The MnO-exchanged Mg-Al-hydrotalcite (Mg/Al = 10) showed high activity in the oxidation of different aromatic and aliphatic aldehydes to their corresponding acids and also showed excellent reusability in the oxidation process which is environmental-friendly.
Keywords: acid; Aldehyde; MnO4-1-exchanged Mg-Al-hydrotalcite catalyst; Oxidation; TBHP

Thermally decomposed Cu-Fe-hydrotalcite. a novel highly active catalyst for o-arylation of naphthol and phenols by aryl halides - Choudhary, Vasant R.; Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar (Catalysis Communications, 2012)
A novel, efficient and environmentally benign method has been reported for the synthesis of diaryl ethers by the o-arylation of napthol or phenols with aryl halides in dimethylformamide (as a solvent) under reflux, using a novel heterogeneous catalyst (having redox properties), obtained from thermal decomposition of Cu-Fe at 600 degrees C in the absence of externally added base. The catalyst comprises Cu(II) and Fe(III) species (oxides and hydroxides), which are uniformly distributed during the catalyst formation. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Aryl halides; C-O cross coupling reaction; Cu-Fe-hydrotalcite; Naphthol; o-Arylation; Phenols

Epoxidation of styrene by t-butyl hydroperoxide over gold nanoparticles supported on Yb2O3: effect of gold deposition method, gold loading, and calcination temperature of the catalyst on its surface properties and catalytic performance - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, N. S.; Uphade, B. S.; Bhargava, Suresh Kumar (Journal of Catalysis, 2013)
Surface properties and epoxidation performance of Au/Yb2O3 catalyst are influenced by the method of gold deposition [viz. deposition-precipitation (DP), homogeneous deposition-precipitation (HDP) or impregnation], gold loading (0.9-6.6 wt%), and the catalyst calcination temperature (400-900 degrees C)]. The catalyst showed the best epoxidation performance when it was prepared by the HDP method and calcined at 500 degrees C. The Au/Yb2O3 catalyst even after calcination at 900 degrees C showed good activity and epoxide selectivity. Both Au-0 and Au3+ surface species were found in the catalyst calcined at 800 degrees C, but only Au-0 species were observed at the lower calcination temperatures (<600 degrees C). The selectivity for styrene oxide increased continuously with the reaction temperature (from 75 degrees C to 97 degrees C) and time (1-5 h), indicating that styrene oxide did not undergo secondary reactions under these conditions. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/Yb2O3 catalyst; Epoxidation of styrene; gold nanoparticles; Styrene oxide; tert-Butyl hydroperoxide

Highly efficient catalyst derived from Ni-Fe-hydrotalcite for solvent-free O- or S-acetylation of alcohols, phenols and thiols at room temperature - Choudhary, Vasant R. (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2013)
Solvent-free O-acetylation of alcohols (including secondary and tertiary alcohols) and phenols and S- acetylation of thiols by acetyl chloride with high product yields at room temperature in a very short reaction period can be easily accomplished using a small amount of solid catalyst obtained from the decomposition (at 600 A degrees C) of Ni-Fe-hydrotalcite. Both the reactions are carried out at room temperature under solvent-free conditions. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity.
Keywords: Acetyl chloride; Alcohols; Ni-Fe- ht derived catalyst; O- and S-acetylation; Phenols; Solvent-free

Suzuki-Miyaura cross-coupling reaction between aryl halides and phenylboronic acids over gold nano-particles supported on MgO (or CaO) and other metal oxides - Dumbre, Deepa K.; Yadav, P. N.; Bhargava, Suresh Kumar; Choudhary, Vasant R. (Journal of Catalysis, 2013)
Gold nano-particles-supported alkaline earth metal oxides, particularly MgO or CaO, show high catalytic activity in the Suzuki-Miyaura cross-coupling reaction in the presence of K2CO3 and DMF (as a solvent). The catalytic activity is strongly influenced by the nature or type of metal oxide support (viz, alkaline earth oxide, Group IIIA metal oxide, transition metal oxide, or rare earth oxide actinide oxide). It is also strongly influenced by the nature of aryl halide (aryl iodide, bromide, chloride, or fluoride), amount of K2CO3 in the reaction mixture and catalyst calcination temperature. Influence of reaction parameters viz, temperature and time and different substituents in aryl halides and/or phenylboronic acids on the biphenyl product yield in the reaction over Au/MgO catalyst has also been investigated. The catalyst showed excellent reusability in the reaction. Moreover, it is ligand-free and also has much lower cost than the commonly used homogeneous and heterogeneous Pd catalysts. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Aryl halides; Au/MgO (or CaO) catalyst; Biphenyls; Gold nano-particles; phenylboronic acids; Suzuki-Miyaura coupling reaction

Calcium oxide supported gold nanoparticles as catalysts for the selective epoxidation of styrene by t-butyl hydroperoxide - Dumbre, Deepa K.; Choudhary, Vasant R.; Patil, Nilesh S.; Uphade, Balu S.; Bhargava, Suresh Kumar (Journal of Colloid and Interface Science, 2014)
Gold nanoparticles are deposited on basic CaO supports as catalysts for the selective conversion of styrene into styrene oxide. Synthetic methods, gold loading and calcination temperatures are varied to permit an understanding of their influence on gold nanoparticle size, the presence of cationic gold species and the nature of interaction between the gold nanoparticles and the CaO support. Based on these studies, optimal conditions are designed to make the Au/CaO catalyst efficient for the selective epoxidation of styrene. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/CaO; Epoxidation of styrene; gold nanoparticles; Homogenous deposition precipitation method; Styrene oxide

Mesoporous, ligand free Cu-Fe solid catalyst mediated CS cross coupling of thiols with aryl halides - Dumbre, Deepa K.; Selvakannan, P. R.; Patil, S. K.; Choudhary, Vasant R.; Bhargava, Suresh Kumar (Applied Catalysis A-General, 2014)
Solid catalyst derived from Cu-Fe hydrotalcite was demonstrated to be a novel, ligandless, efficient and environmentally greener catalyst for the synthesis of diaryl sulfurs from the C-S cross coupling reaction of substituted thiols with different aryl halides. This catalyst has shown higher product yield in the presence of dimethylformamide (as a solvent) and K2CO3 (as a base) at 120 C. Influence of different solvents and bases on the product yield has also been investigated. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. The catalyst has been fully characterized for its surface and bulk properties and the mesoporous CuO:Fe2O3 phase was attributed for its catalytic activity towards S-arylation reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: C-S cross coupling; Cu-Fe-hydrotalcite; S-arylation